A high-performance liquid chromatographic assay for sparfloxacin - Marona, HRN; Schapoval, EES (Elsevier B.V., 1999)
A specific and sensitive high-performance liquid chromatographic procedure was developed for the assay of sparfloxacin in raw material and tablets. It was also found that the excipients in the commercial tablet preparation did not interfere with the assay. The method validation yielded good results and included the range, linearity, precision, accuracy, specificity and recovery. This method can also be applied to stability studies. (C) 1999 Elsevier B.V. B.V. All rights reserved.
Keywords: fluoroquinolone; HPLC; quality control; sparfloxacin